UI/UX Designing of an Indonesian Language Writing Educational Game for Elementary School Students Using a Human Centred Design Method - Luthfi Syukriansyah Fitra; Chanifah Indah Ratnasari (Kresnamedia Publisher, 2023)
Based on previous research conducted on elementary school students, it was found that there are still many errors in the use of EYD or KBBI rules, such as errors in the use of capital letters and the use of words. The lack of learning media outside of school triggers students' lack of understanding. Using technology-based learning media in games is exciting and can help improve students' understanding outside school. Using educational games as out-of-school learning media has several advantages, namely ease of access and higher student interest in playing. In developing games, an attractive appearance is needed and is the need of elementary school students. This is adequate and can increase students' interest in using the game as an out-of-school learning media. Therefore, an appropriate design method is needed to design the appearance to be attractive and in accordance with the needs of students, one of which is Human-Centered Design (HCD). This method involves users directly during the design process. By applying the HCD method, this research aims to design the interface of the